Factores motivacionales que influyen en la satisfacción laboral de los colaboradores del área administrativa de la empresa Hidrandina S.A. sede Trujillo. - Rojas Cruz, Katerin Alexzandra (2018)
The purpose of this research was to determine the relationship between the motivational factors with the job satisfaction in the collaborators of the administrative area of the company Hidrandina S.A. headquarters Trujillo, 2018. It is of correlational descriptive type and transversal character, the sample was consisted by 43 collaborators of the different areas to which they were applied an instrument: self-elaboration questionnaire consisting of two parts, the first of the motivational factors, based on the theory of Herzberg (1959) and the second part of the work satisfaction based on the proposal of Palma (2005). It was found that the significance of the task, the recognition, professional advancement, and autonomy of work, are motivational factors average (60%,51% 49%, y53% respectively), also the self-realization is a high motivational factor (67%), on the other hand, the Job satisfaction reaches the average level (67%) in the collaborators of the administrative area of the company Hidrandina S.A. It is concluded that there is a significant relationship (P < 0.05) between the significance of the task, the recognition, professional advancement, labor autonomy and self-realization where (P = 0.005; p = 0.001; p = 0,013; p = 0,013 and P = 0,021 respectively) as motivational factors in the work satisfaction of the collaborators of the administrative area of the company Hidrandina S.A., headquarters Trujillo, 2018. This report will make known the problematic reality, background, theoretical bases, conceptual framework, the scientific problem, justification, hypothesis, objectives, the methodology making known the population and sample, the methods, techniques and instruments used for the achievement of objectives raised, culminating with the Presentation of results, conclusions and recommendations.